2020
DOI: 10.1021/acssuschemeng.0c02351
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Divanillin As a Precursor for Formulating Biobased Epoxy Resin

Abstract: Divanillin (DV), which can be facilely synthesized via vanillin dimerization, was employed as a building block to formulate epoxy resin. DV was synthesized through a novel approach in hot water in only 30 min with a yield of 87.5%. The process involved FeSO4-catalyzed Na2S2O8-based oxidative coupling of vanillin without any purification, followed by treatment with biobased epichlorohydrin. Epoxidized-divanillin (EDV) was cured with the petroleum-based, commercially available hardener isophorone diamine (IPDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 55 publications
1
52
0
1
Order By: Relevance
“…Epoxy contents of epoxidized lignin samples were measured by 1 H NMR according to a previously reported method [64] . Each epoxidized lignin sample (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Epoxy contents of epoxidized lignin samples were measured by 1 H NMR according to a previously reported method [64] . Each epoxidized lignin sample (ca.…”
Section: Methodsmentioning
confidence: 99%
“…38 Under the catalysis of Na 2 S 2 O 8 , two equivalent vanillin can also be coupled directly and the aldehyde group could be retained. 39 Jian and Weng et al developed a trifunctional bio-based epoxy resin bearing triazine structure through the conversion of aldehydes to cyan and cyclization (Scheme 4(B)). After curing by 4,4 0 -diaminodiphenyl sulfone, the thermosets showed excellent T g (300 C) and considerable mechanical properties (53.9% and 14.3% higher respectively) compared to the DGEBA counterpart.…”
Section: High Performance Bio-based Epoxy Resinmentioning
confidence: 99%
“…68 By Michael addition, three amines were integrated into acrylic epoxy soybean oil, which can be used for simply regulating the properties of polymers. 69 In addition, utilizing the curing system with amine derivatives containing aliphatic ring, 39 hetero ring, 21 and aromatic ring, 67 could improve the performance of mixture.…”
Section: S C H E M E 3 Synthesis Routes Of Limonene-based Epoxy Monomersmentioning
confidence: 99%
“…Divanillin is readily made via enzymatic oxidative dimerization of vanillin on horseradish peroxidase ( Armoracia rusticana ) [ 78 ]. Alternatively, it can be produced oxidative coupling by using laccase [ 79 , 80 , 81 ], iron(III) chloride [ 82 ], and persulfate salts [ 83 , 84 , 85 ]. For instance, Fang et al has very recently showed that sodium persulfate (Na 2 S 2 O 8 ) is an effective persulfate salt for the synthesis of divanillin due to its high water solubility and inexpensiveness [ 85 ].…”
Section: Production Of Polymers From the Lignin-derived Aromatic Amentioning
confidence: 99%
“…Bisphenols are precursors of a wide variety of polymers including polyesters [ 79 ], polycyanurates [ 72 ], polycarbonates [ 72 ], and epoxy resins [ 85 , 94 ] that are made through simple modifications of the structure of bisphenols. Two strategies have been available to make bisphenols from vanillin.…”
Section: Production Of Polymers From the Lignin-derived Aromatic Amentioning
confidence: 99%